WIND ENERGY - ORIPOVA DILNOZA KARIMJON KIZI; YUSUPOV ABDURASHID KHAMIDILLAEVICH (TADQIQOTLAR, 2025)
Annotation: This scientific work discusses the natural source of wind energy, its operating principles, advantages, and disadvantages. The study highlights the technology of generating electricity through wind turbines, their environmental cleanliness, and economic efficiency. It also analyzes the potential and prospects for the development of wind energy in the context of Uzbekistan. Furthermore, the necessity of transitioning to renewable energy sources and the role of wind energy in sustainable development are emphasized.